Comparison of Incidence and Clinical Outcomes of COVID-19 among Healthcare Workers in the Prevaccination and Post-vaccination Periods: A Real-world Impact Study - Serkan Surme; Betul Copur; Osman Faruk Bayramlar; Gulsah Tuncer; Yusuf Emre Ozdemir; Filiz Pehlivanoglu; Gonul Sengoz (Haseki Tıp Bülteni, 2022)

(untitled)
Aim:Real-life data on the effect of coronavirus disease-2019 (COVID-19) vaccination is limited. We aimed to compare the incidence of COVID-19 among healthcare workers (HCWs) in the pre-vaccination and post-vaccination periods during the COVID-19 pandemic and identify associated factors for COVID-19 development.Methods:In this single-center and cross-sectional study, HCWs employed in a tertiary care hospital were included. Pre-vaccination (14 October, 2020 and 14 January, 2021) and post-vaccination periods (1 March, 2021 and 1 June, 2021) were compared. A subgroup analysis was performed on HCWs without a previous history of COVID-19. Additionally, univariate regression analysis of COVID-19 development in the post-vaccination period was performed.Results:Of 2,922 HCWs, 2,096 (71.7%) were vaccinated. The incidence of COVID-19 was higher in the pre-vaccination period (16.3%) than in the post-vaccination (6.6%) (p<0.01). In the subgroup analysis, the incidence of COVID-19 was 16.6% in the pre-vaccination period and 8.1% in the post-vaccination period (p<0.01). Previous history of COVID-19 (p<0.01) and double-dose vaccination (p<0.01) were associated with a decreased risk of COVID-19 development.Conclusion:This study demonstrates the real-life impact of COVID-19 vaccination in reducing disease development and preventing poor clinical outcomes in a setting where the vaccination rate among HCWs was fairly low.